Effects of rifaximin in fructose-induced steatohepatitis in rats - Celik, Nese Cabuk; Goc, Rumeysa Yilmaz; Bahcecioglu, Ibrahim Halil; Ozercan, I. Hanifi; Tuzcu, Mehmet; Ilhan, Necip; Şahin, Kazım (Kare Publ, 2025)
Background and Aim: Metabolic-dysfunction-associated steatotic liver disease and its related mortality are increasing worldwide. This study evaluated the potential of rifaximin in preventing and treating steatohepatitis induced by a high-fructose diet by modulating intestinal pathology. Materials and Methods: Forty-two rats were randomly divided into six groups: one group received a normal diet, another was fed a fructose diet, two groups received rifaximin (once or three times weekly) along with a fructose diet, and the remaining two groups were given rifaximin (once or three times weekly) with a normal diet. After eight weeks, liver tissues were examined for malondialdehyde, tumor necrosis factor-alpha, nuclear factor-xB, and nuclear factor erythroid 2-related factor 2 using Western blot analysis, while blood samples were analyzed for uric acid, liver enzymes, triglycerides, and cholesterol; plasma tumor necrosis factor-alpha was measured by ELISA. Results: The fructose diet group showed significant increases in body and liver weights, ballooning degeneration, lobular inflammation, and macrovesicular steatosis. Metabolic dysfunction-associated steatotic liver disease developed in 21 rats, yet steatohepatitis was observed only in the fructose-only group. Biochemical markers, including liver enzymes, triglycerides, and cholesterol, were significantly elevated in the fructose group. Moreover, plasma and tissue tumor necrosis factor-alpha and nuclear factor-xB levels were higher in the fructose group (p=0.03), while Nrf-2 levels were elevated in the rifaximin-treated groups (p=0.043). Additionally, MDA levels were markedly increased in the fructose-only group (p=0.033) and decreased dose-dependently with rifaximin treatment (p=0.029). Conclusion: These findings suggest that rifaximin's anti-inflammatory and antioxidant effects may alleviate fructose-induced steatohepatitis, although further clinical studies are warranted.
Keywords: Fructose; non-alcoholic fatty liver disease; rifaximin